2014
DOI: 10.2105/ajph.2013.301572
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Residency Status and Census Tract Socioeconomic Status as Determinants of Colorectal Cancer Outcomes

Abstract: Future efforts should focus on developing interventions and policies that target rural residents and lower SES areas to eliminate disparities in CRC-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 55 publications
9
97
1
5
Order By: Relevance
“…These findings expand on previously reported state disparities in colorectal cancer death rates (3) and are consistent with recent research linking rural residence with increased risk of colorectal cancer death (12,13). The trends in Hotspots 1 and 3 are also compatible with the historical shift in the burden of colorectal cancer from more to less affluent individuals (5).…”
Section: Discussionsupporting
confidence: 89%
“…These findings expand on previously reported state disparities in colorectal cancer death rates (3) and are consistent with recent research linking rural residence with increased risk of colorectal cancer death (12,13). The trends in Hotspots 1 and 3 are also compatible with the historical shift in the burden of colorectal cancer from more to less affluent individuals (5).…”
Section: Discussionsupporting
confidence: 89%
“…Variables of interest included race, sex, age at diagnosis, date of diagnosis, tumor-related information (stage and grade), treatment type, last date of follow-up and vital status at last follow-up. Using the corresponding CT, 2000 U.S. Census data and Rural Urban Commuting Area (RUCA) codes from the U.S. Department of Agriculture were merged with GCCR data (24,25). RUCA codes were used to classify each patient as urban, suburban, or rural (26)(27)(28).…”
Section: Study Variablesmentioning
confidence: 99%
“…While these effects were diminished in sensitivity analyses among women with confirmed HER2 status, regional variations in other unrelated aspects of cancer care and outcomes are well-documented. 4042 Regional variation in GEP testing could reflect continued clinical uncertainty or professional disagreements among oncologists regarding the utility of GEP testing. Finally, we found that testing rates were higher for patients with greater out of pocket burden for pharmacy costs.…”
Section: Discussionmentioning
confidence: 99%